Effect of caffeine on clozapine pharmacokinetics in healthy volunteers - Hägg, Staffan (Blackwell Science Inc, 2000)
AIMS: To assess the effects of caffeine on the pharmacokinetics of clozapine in healthy volunteers. METHODS: This was an open label randomized crossover study in 12 nonsmoking healthy male volunteers. The subjects received a single oral dose of 12.5 mg clozapine in each phase with or without concomitant intake of caffeine (mean dose: 550 mg day(−1), range: 400–1000 mg day(−1)). Serum concentrations of clozapine and its metabolites desmethyl-clozapine and clozapine-N-oxide were measured during a 48 h period in each phase. In addition, serum concentrations of caffeine and the metabolite paraxanthine were monitored. RESULTS: A 19% increase in mean clozapine AUC(0,∞) (P = 0.05) and a 14% decrease of mean oral clearance of clozapine were observed during concomitant intake of caffeine (P = 0.05) compared with intake of only clozapine. Statistically significant decreases of mean ratios between AUC(0,12h) for desmethyl-clozapine and AUC(0,12h) for clozapine (−18%), and between AUC(0,12h) for clozapine-N-oxide and AUC(0,12h) for clozapine (−23%) were observed during the caffeine phase (P = 0.03 and 0.02, respectively). Oral clearance of clozapine and the ratio AUC(0,12h) for desmethyl-clozapine/AUC(0,12h) for clozapine were correlated with the paraxanthine/caffeine ratio in serum after intake of caffeine (r(s) = 0.62; P = 0.03 and r(s) = 0.77; P = 0.003, respectively). CONCLUSIONS: These results suggest that caffeine in daily doses of 400–1000 mg inhibits the metabolism of clozapine to an extent that might be clinically significant in certain individuals.